El procedimiento abreviado frente a los principios constitucionales del procesado. - Sánchez Naranjo, Cristina Estefanía (2024)
The present study analyzes the abbreviated procedure against the constitutional principles, it has specific rules determined in article 635, of the Comprehensive Criminal Organic Code, requires that the person prosecuted admit and recognize that he is guilty of the crime accused against him in order to obtain a reduction in the custodial sentence; That is, he has to incriminate himself, contravening constitutional principles such as the prohibition of self-incrimination, innocence and equality, which are recognized in the Constitution of the Republic of Ecuador and the COIP. The abuse of this procedure by the Prosecutor's Office can have an impact on the legal status of the accused, causing an innocent person to end up accepting to be sentenced as responsible for the criminal act within this procedure, as a result of the distrust that in an ordinary trial it is applied. the maximum sanction, being disadvantaged in the face of the malicious actions of the administration of justice. The research was developed under the quantitative and qualitative method, which allowed the collection of scientific data, as well as the interpretation of the results obtained with respect to the abbreviated procedure and the constitutional principles that assist the accused, in addition the method was applied. legal, documentary that allowed supporting theoretical framework; The type of research applied was descriptive, doctrinal and historical; As a research technique, a survey was used aimed at criminal lawyers in free practice, and a survey of Judges of the Criminal Judicial Unit of the Guaranda Canton. Keywords: Self-incrimination, Due process, Constitutional principles, Presumption of innocence, Abbreviated procedure.